Delphi study to develop maternal depression training materials for cadres - Endang Retno Surjaningrum; Tino Leonardi; Fitri Andriani; Tiara Diah Sosialita; Bani Bacan Hacantya Yudanagara; Husnul Mujahadah (International Journal of Public Health Science (IJPHS), 2023)
This study aimed to obtain themes and constructs to develop modules and training curricula for cadres for the detection of depression in pregnant and breastfeeding mothers in Surabaya, Indonesia. The Delphi method through three stages was applied: i) searching for academic and non-academic references; ii) compiling themes and constructs based on the findings of the first phase and distributing them to expert panel; and iii) concluding a consensus according to the guidelines. The panel approved two training objectives, five training materials, six training methods, two training time, two training duration, two training evaluation method, and six trainer qualifications. The findings can be the basis for developing modules and curricula to detect maternal depression in pregnant and breastfeeding women for cadres in Indonesia.